Outcome of Obturator Nerve Block by Inguinal and Transvesical Approach in Transurethral Resection of Bladder Tumor (Bangladesh Journal of Urology, 2020)
Introduction and aim of the study : Spinal anaesthesia for transurethral resection of bladder tumor (TURBT) does not prevent unintended stimulation of the obturator nerve when electro resection is performed on the lateral and Postero-lateral wall of the bladder. It results in muscle contraction of the adductor muscles of the thigh, which may lead to perforation of bladder wall with the resectoscope loop. The aim of the study was to compare the outcome of obturator nerve block by inguinal and transvesical approach.Materials and Methods: A prospective experimental study was done in the department of Urology Dhaka Medical College Hospital during the period of November 2016 to April 2018. Total 60 Patients were included for the study as per inclusion and exclusion Criteria. Patients were than allocated purposively into two groups by simple random sampling. Group A consisted of 30 patients where obturator nerve block (ONB) was done by transvesical approach and Group B also consisted of 30 patients where ONB was done by inguinal approach.Results: In the present study, the baseline characteristics of the patients in Group-A and Group-B were almost similar having no statistically significant difference. Obturator jerk more frequently occurred in group-B, in 13 (56.37%) patients following TURBT compared to Group-A, where 05(16.67%) patients developed obturator jerk. The intergroup difference was statistically significant (p0.05). There was no incidence of bladder wall perforation in group-A, wherears this complication occurred in 02 (06.67%) cases of Group-B (p>0.05). Mean operative time in Group-A and group-B is 50.46 (±11.64) and 59.10 (±15.83) respectively (p